IMMIGRANTS’ USE OF LANGUAGE FOR PROFESSIONAL PURPOSES IN A HOST COUNTRY: IMPLICATIONS FOR ADULT EDUCATION - Ahrens, Andreas; Zascerinska, Jelena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
By 2050 the flow of climate immigrants is repeatedly predicted to be about 200 million. Immigrants’ employment in a host country has become a hot issue. To empower immigrants’ employability, structural features, e.g. adult education, can assist with providing a proper training to immigrants. The aim of the present paper is to carry out an empirical study on immigrants’ use of language for professional purposes in a host country underpinning elaboration of implications for adult education. The empirical study was carried out at Klaipeda University, Klaipeda, Lithuania, on the 24th October 2019. Focus interview served as the basis for data collection. Theoretical analysis results in the establishment of inter-connections between immigrants’ use of mother tongue, foreign language as well as host country’s language at work in a host country. The conclusion is drawn that the majority of immigrants uses their mother tongues at work in a host country. The empirical study reveals that local companies employ immigrants for establishing business connections between the immigrants’ host country as well as immigrants’ origin country. The paper’s novel contribution is the newly formulated implications on immigrants’ use of language for professional purposes for adult education. Directions of future work are proposed.